2017
DOI: 10.15230/scsk.2017.43.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Anti-melanogenesis Active Constituents from the Extracts of Carpinus turczaninowii Leaves

Abstract: Melanin synthesis inhibition activities were investigated for the extracts prepared from the leaves of Carpinus turczaninowii (C. turczaninowii) by using B16F10 melanoma cells. As a result, the ethanol extract (100 µg/mL) showed 72.2% inhibition activities without cell toxicities in MTT assays. For the solvent fractions (n-hexane, ethyl acetate, n-butanol, water), the most potent activities were observed at the ethyl acetate fraction. To isolate the active constituents, the ethyl acetate fraction was further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…C. turczaninowii belongs to the Betulaceae family; it is a deciduous woody plant usually grown in the Jeju islands of Korea [19]. Very few recent studies have reported the antioxidant capacity and anti-inflammatory effects of leaves and branches of C. turczaninowii , thereby suggesting the potential use as a therapeutic agent for inflammatory diseases [15161722]. As reported in other studies [15161722], the current study also evaluates the antioxidant capacity of the C. turczaninowii extract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C. turczaninowii belongs to the Betulaceae family; it is a deciduous woody plant usually grown in the Jeju islands of Korea [19]. Very few recent studies have reported the antioxidant capacity and anti-inflammatory effects of leaves and branches of C. turczaninowii , thereby suggesting the potential use as a therapeutic agent for inflammatory diseases [15161722]. As reported in other studies [15161722], the current study also evaluates the antioxidant capacity of the C. turczaninowii extract.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that NO is one of the inflammatory mediators, NO generation from the cells were slightly, but dose-dependently decreased, after 24 h C. turczaninowii extract treatment (25 to 200 µg/mL) [15]. Kang et al [17] also showed dose-dependent reduction of NO production from LPS-stimulated RAW264.7 cells (1 µg/mL of LPS) after exposure to the extract (12.5 to 100 µg/mL). In addition, in their study of NO inhibition by 260 types of Jeju plant extracts, Yang et al reported about 69% inhibition of NO and 80% viability of RAW264.7 cells after exposure to 100 µg/mL of C. turczaninowii extract [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations